Economic valuation of the environmental water service of the community of La Pita, Manabí - Ecuador. (Revista Científica Ciencias Naturales y Ambientales, 2023)
There are significant supply and management issues with the water resource. An extensive range of anthropogenic activities are carried out in the La Pita community in Manabi, Ecuador, and as a result, the research’s goal was to evaluate the community’s environmental water service. Surveys were used to establish the socioeconomic characteristics of the population and the contingent value method was used. After gathering the data, the logit model was used to calculate the water service’s economic value. The ArcGIS 10.4.1 Geographic Information System was used to georeference each of the 24 water sources that serve 32 residences. La Pita’s water service is economically valued at $195.00 per month. This study has demonstrated that it is possible to value environmental services and produce ideas aimed at enhancing rural residents’ quality of life.
Keywords: Water resource; Rural community; Contingent valuation; Logit model